Dye-sensitized solar cell of improved photo-anode structure - THE INVENTOR HAS WAIVED THE RIGHT TO BE MENTIONED (2017)
The invention relates to a dye-sensitized solar cell of an improved photo-anode structure. The solar cell comprises a photo-anode, a counter electrode, and electrolyte. The counter electrode is arranged opposite to the photo-anode, and is formed by printing platinum on the upper surface of an FTO substrate. The electrolyte is arranged between the photo-anode and the counter electrode. Dye sensitizers are absorbed on the surface of the photo-anode and are N719 ruthenium dyes. The redox couple in the electrolyte is I<->/I3<->. The photo-anode comprises the FTO substrate. A SnO2 particle layer is arranged on the surface of the FTO substrate. A SnO2 nanowire layer is arranged on the surface of the SnO2 particle layer. 本申请涉及种改进型光阳极结构的染料敏化太阳能电池，该染料敏化太阳能电池包括光阳极、对电极、电解液；其中，该对电极与光阳极对置设置，该对电极是在FTO基底的上表面印刷有铂形成的；电解液设置在光阳极与对电极之间；该光阳极表面吸附有染料敏化剂，该染料敏化剂为N719钌染料，该电解液中氧化还原对为I/I；该光阳极包括FTO基底，在FTO基底表面设有SnO颗粒层，在SnO颗粒层表面设有SnO纳米线层。